FEATURES OF THE FRAME ‘GREEN ECONOMY’ IN THE ENGLISH-SPEAKING POLITICAL DISCOURSE - Jacopo Vigna-Taglianti; Elizaveta N. Sidorova; Elena N. Shirlina (Sovremennye Issledovaniâ Socialʹnyh Problem, 2022)
Background. Recently, the issues of sustainable economic development and environmentally friendly production have become an important part of the political agenda in various countries. The public image of the ‘green economy’ is formed in the political discourse, so that is where its framing takes place. However, the features of the frame ‘green economy’ in public speeches of prominent political figures have not gotten enough attention yet.